2015
DOI: 10.1021/acs.langmuir.5b01737
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluorocarbon and Hydrocarbon Chain Lengths in Hybrid Surfactants for Supercritical CO2

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms The W0 value of 80 is the highest for a HC-FC hybrid surfactant, matching the highest value reported for a FC surfactant which contained more FC groups. High-pressure SANS measurements from FCmHCn/D2O/CO2 microemulsions were consistent with growth of the microemulsion droplets with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(88 citation statements)
references
References 38 publications
3
85
0
Order By: Relevance
“…Fluorosurfactants are used as additives for paints, coatings, and fire extinguisher foams, wetting agents, cleaners for hard surfaces, plane hydraulic fluids, emulsifying and dispersing agents, surface protectors, etc. [14][15][16][17][18][19][20][21] The most investigated fluorinated surfactants are anionic [21][22][23] and non-ionic. 12,13 The presence of both hydrophilic heads and fluorinated chain(s) in their structures makes some fluorosurfactants also efficient in stabilisation of water-in-CO 2 microemulsions.…”
mentioning
confidence: 99%
“…Fluorosurfactants are used as additives for paints, coatings, and fire extinguisher foams, wetting agents, cleaners for hard surfaces, plane hydraulic fluids, emulsifying and dispersing agents, surface protectors, etc. [14][15][16][17][18][19][20][21] The most investigated fluorinated surfactants are anionic [21][22][23] and non-ionic. 12,13 The presence of both hydrophilic heads and fluorinated chain(s) in their structures makes some fluorosurfactants also efficient in stabilisation of water-in-CO 2 microemulsions.…”
mentioning
confidence: 99%
“…For example, DeSimone et al 17 reported that dendrimers with a fluorinated shell were soluble in liquid CO2, and could extract an ionic dye methyl orange in the dendrimer core from water phase. Liu et al 18 19 The optimal HC-tail and FC-tail length in this hybrid surfactant was found to be n = 4 and m = 6 respectively (i.e. FC6-HC4).…”
Section: Introductionmentioning
confidence: 84%
“…The family of compounds Nohead FC6-HCn (n = 2, 4, 6) and Nohead HC6-HC4 are the intermediates obtained before the sulfonation step used to obtain the hybrid surfactants sodium 1-oxo-1- as shown in Figure 1. All of these compounds were synthesized and purified as described in the earlier paper 19…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations